2015
DOI: 10.3390/f6113868
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Phoracantha semipunctata in Response to Severe Drought in a Mediterranean Eucalyptus Forest

Abstract: Extreme climatic events, including droughts and heatwaves, can trigger outbreaks of woodboring beetles by compromising host defenses and creating habitat conducive for beetle development. As the frequency, intensity, and duration of droughts are likely to increase in the future, beetle outbreaks are expected to become more common. The combination of drought and beetle outbreaks has the potential to alter ecosystem structure, composition, and function. Our aim was to investigate a potential outbreak of the nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…Ecosystems may change most rapidly and profoundly in regions experiencing compound events or multiple stress periods, occurring concurrently, or in quick succession . In the Northern Jarrah Forest, and elsewhere, the combination of drought and warming has corresponded with beetle outbreaks (Seaton et al 2015), forest fires (Gouveia et al 2016), and associated widespread terrestrial carbon losses (Berner et al 2017). Not only do these processes have an impact on forest structure and functioning, but also the potential to profoundly alter our future atmosphere and climate (Zemp et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystems may change most rapidly and profoundly in regions experiencing compound events or multiple stress periods, occurring concurrently, or in quick succession . In the Northern Jarrah Forest, and elsewhere, the combination of drought and warming has corresponded with beetle outbreaks (Seaton et al 2015), forest fires (Gouveia et al 2016), and associated widespread terrestrial carbon losses (Berner et al 2017). Not only do these processes have an impact on forest structure and functioning, but also the potential to profoundly alter our future atmosphere and climate (Zemp et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A sudden and unprecedented forest collapse was observed in the Northern Jarrah Forest (NJF) of SWWA following record dry and heat conditions in 2010/2011, with the death and collapse of midstorey and overstorey jarrah and marri crowns observed following this period of sudden and severe drought (Matusick et al, 2013). The four tree deaths at the Brunswick Junction forest site that were not associated with canker were attributed to drought induced mortality, with high feeding damage and infestation levels by the native Eucalyptus longhorned borer (Phorocantha semipunctata Fabricius) providing further evidence that these deaths resulted from water stress (Seaton, Matusick, Ruthrof, & Hardy, 2015). under severe water stress, B. mediterranea develops rapidly within the xylem with the potential to kill the entire host (Desprez-Loustau et al, 2006;Vannini & Valentini, 1994).…”
Section: Discussionmentioning
confidence: 88%
“…The SWWA has experienced a persistent trend of declining annual rainfall and increasing temperatures since the 1970s (Bates, Hope, Ryan, Smith, & Charles, 2008), which is projected to continue into the future (CSIRO & BOM 2007, IPCC 2013. The four tree deaths at the Brunswick Junction forest site that were not associated with canker were attributed to drought induced mortality, with high feeding damage and infestation levels by the native Eucalyptus longhorned borer (Phorocantha semipunctata Fabricius) providing further evidence that these deaths resulted from water stress (Seaton, Matusick, Ruthrof, & Hardy, 2015). A sudden and unprecedented forest collapse was observed in the Northern Jarrah Forest (NJF) of SWWA following record dry and heat conditions in 2010/2011, with the death and collapse of midstorey and overstorey jarrah and marri crowns observed following this period of sudden and severe drought (Matusick et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Large areas of stressed and dying trees associated with a drought event, leading to widespread attack by P. semipunctata in Southwestern Australia jarrah forest, showed that tree health was critical for determining the intensity of borer emergence [36]. To estimate the borer's population size and better understand its behaviour, these drought-stressed trees in the Northern Jarrah Forest (NJF) provided an opportunity to determine how tree characteristics shaped the within-tree distribution and affected the survival of P. semipunctata in Australia.…”
Section: Introductionmentioning
confidence: 99%